An Analysis of Code Switching and Code Mixing on Teacher’s Function of Language Utterances - Evirita Roslina Sitinjak; Erika Sinambela; Cici Melysa; Eliana Sitompul (Jayapangus Press, 2020)
This study discusses code switching and code mixing in the process of teaching English. This study aimed to investigate the teacher's speech containing code switching and code mixing in classroom. This study uses a qualitative descriptive design. Data were analyzed based on Hoffman's theory in finding the type of code switching and mixing code used by the teacher in the classroom, and found the type of language function in the pronunciation of code switching and code mixing and also the teacher's reasons for using code switching and code mixing. Data were taken from classroom observations at the Global Prima School and interviews with teachers to find out the reasons for teachers using code switching and mixing code in the learning process of English. Data were collected in connection with code switching observations and code mixing when teaching English. The results showed that there were 89 code switching consisting of 72 inter-sentential codes or 80.90%. For emblematic code switching there are 11 utterances or 12.36%. For the establishing continuity of the previous speaker there are 6 utterances or 6.47%. On the other hand, there are 107 code mixing consisting of 103 intra-sentential code mixing or 96.26%. For intra-lexical code mixing, there are 4 utterances or 3.74%. In involving a change of pronunciation, the author found that the data was 0%. Most code mixing occurs when teaching English. For the language functions used by the teacher in terms of code switching and code mixing, there are four functions found in this study, they are personal functions, interpersonal functions, directive functions and referential functions, and referential functions is the most used by the teacher in their speech. There are no utterances that contain imaginative functions. There are five reasons why teachers use code switching and mixing code, namely: interjection, the intention of clarifying the speech content for interlocutors, because of real lexical need, expressing group identity and influencing of the first speaker.